Comparison of triple dose versus standard dose gadolinium-DTPA for detection of MRI enhancing lesions in patients with primary progressive multiple sclerosis. Issue 5 (November 1995) - Filippi, M; Campi, A; Martinelli, V; Colombo, B; Yousry, T; Canal, N; Scotti, G; Comi, G
Abstract : This study was performed to evaluate whether a triple dose of gadolinium-DTPA (Gd-DTPA) increases the sensitivity of brain MRI for detecting enhancing lesions in patients with primary progressive multiple sclerosis (PPMS). T1 weighted brain MRI was obtained for 10 patients with PPMS in two sessions. In the first session, one scan was obtained five to seven minutes after the injection of 0.1 mmol/kg Gd-DTPA (standard dose). In the second session, six to 24 hours later, one scan before and two scans five to seven minutes and one hour after the injection of 0.3 mmol/kg Gd-DTPA (triple dose) were obtained. Four enhancing lesions were detected in two patients when the standard dose of Gd-DTPA was used. The numbers of enhancing lesions increased to 13 and the numbers of patients with such lesions to five when the triple dose of Gd-DTPA was used and to 14 and six in the one hour delayed scans. The mean contrast ratio for enhancing lesions detected with the triple dose of Gd-DTPA was higher than those for lesions present in both the standard dose (P < 0.0009) and the one hour delayed scans (P = 0.04). These data indicate that with a triple dose of Gd-DTPA many more enhancing lesions can be detected in patients with PPMS. This is important both for planning clinical trials and for detecting the presence of inflammation in vivo in the lesions of such patients.